2018
DOI: 10.37358/rc.18.5.6286
|View full text |Cite
|
Sign up to set email alerts
|

Combined Approach of the Anterior Skull Base in Sinonasal Tumours

Abstract: Malignancies of the nasal cavity and the paranasal sinuses are rare, counting for less than 3 % of the ENT-cancers. The insidious onset of these tumours with non-specific symptoms often leads to a delayed diagnostic. Advanced disease stage combined with the complex anatomy of the sinonasal cavities and anterior skull base encouraged surgeons to extend beyond the boundaries the classic surgical techniques. Surgical approaches to anterior skull base lesions can be divided into open approches: craniofacial, subcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Our study showed statistically significant higher levelsof TAC in the healthy group compared to groups with CSOM with or without cholesteatoma, thus demonstrating the existence of an imbalance between oxidant-antioxidant systems. Vascular proliferation, leukocyte infiltration, epithelial thickening, local oedema was linked to the overproduction of oxidants and the tissue damage in the middle ear [12][13][14]. Some studies show a decrease in the level of oxidative stress by ventilation tube insertion that decrease the local inflammation [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…Our study showed statistically significant higher levelsof TAC in the healthy group compared to groups with CSOM with or without cholesteatoma, thus demonstrating the existence of an imbalance between oxidant-antioxidant systems. Vascular proliferation, leukocyte infiltration, epithelial thickening, local oedema was linked to the overproduction of oxidants and the tissue damage in the middle ear [12][13][14]. Some studies show a decrease in the level of oxidative stress by ventilation tube insertion that decrease the local inflammation [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…One aspect worth noting is the succession of chemotherapy and radiotherapy. In the past years oncologists opted for initial radiotherapy followed by surgery and then chemotherapy, but histology studies dismantled this theor y demonstrating that after radiotherapy the fibrosis of irradiated tissues with local hypoperfusion, do not allow chemotherapy drugs to penetratethe remaining tumour tissue [19][20][21][22].…”
Section: Table 2 Therapy In Rhinosinusal Malignanciesmentioning
confidence: 99%
“…It is important to know that by respecting the measures of oral hygiene it is intended the removal of the bacterial plaque from the hard structures but the oral environment will never be a sterile one. Maintaining the balance of the oral microbial ecosystem is essential because commensal bacteria have a protective role, helping the immune response and preventing the development of other pathogenic species that make the organism ill [19][20][21][22].…”
mentioning
confidence: 99%